Hypokalemia as a risk factor for prolonged QT interval and arrhythmia in inherited salt-losing tubulopathy - Seong Ryeong Kang; Yo Han Ahn; Hee Gyung Kang; Naye Choi (Korean Society of Pediatric Nephrology, 2023)
Purpose To analyze electrocardiograms (ECGs) of patients with a salt-losing tubulopathy (SLT) and to determine the frequency and risk factors for long QT and arrhythmia. Methods A total of 203 patients aged <19 years with SLT, specifically Bartter syndrome and Gitelman syndrome, who had a 12-lead ECG were included in this retrospective study. We analyzed the presence of an arrhythmia or prolonged corrected QT (QTc) on ECGs obtained for these patients. Demographic and laboratory data were compared between patients with abnormal and normal ECG findings. Results Out of the 203 SLT patients, 38 (18.7%) underwent electrocardiography and 10 (40.0%) of 25 patients with inherited SLT had abnormal ECG findings, including prolonged QTc and arrhythmias. The abnormal ECG group had significantly lower serum potassium levels than the normal group (median [interquartile range]: 2.50 mmol/L [2.20-2.83] vs. 2.90 mmol/L [2.70-3.30], P=0.036), whereas other serum chemistry values did not show significant differences. The cutoff level for a significant difference in QTc interval was serum potassium level <2.50 mmol/L. One cardiac event occurred in a 13-year-old boy, who developed paroxysmal supraventricular tachycardia and underwent cardiac ablation. No sudden cardiac deaths occurred in this cohort. Conclusions The incidence of ECG abnormalities in patients with inherited SLT was 40.0%, whereas the ECG screening rate was relatively low (18.7%). Therefore, we recommend ECG screening in patients with inherited SLT, especially in those with serum potassium level <2.50 mmol/L.